Prepare SME in Facing AEC 2015 through English Training Program to Obtain the Export Market - Rianto Nurcahyo; Raja Halim Harahap; Didiet Gharnaditya (Bina Nusantara University, 2015)
Entering the era of globalization, better known as free market requires every individual to prepare reliable resources, especially in the field of Science and Technology. In order to master these demands, adequate knowledge is required in dealing with the demands of a globalized world that is full of competition. In this regard, the role of the English language is required both in mastering communication technologies and to interact directly; moreover, the presence of the media especially the Internet will force people to learn English. As a means of global communication, English should be actively mastered both orally and in written. In an increasingly globalized business world, there are more local Indonesian companies entering into the world market, and growing number of international companies. This research is an attempt to create the roles of exporters, especially the Micro, Small and Medium Enterprises (SMEs) through the products produced by the exporters themselves. Comparing Indonesian export revenue number to other countries, the value of Indonesia's exports is relatively low. One of the constraints faced by exporters is in terms of the ability of a foreign language, namely English. Mastery of English is the main capital to open international trading communication. This research focuses on Quantitative method using chi square analysis, where it can be used to test the relationor the effect of two nominal variables and to measure the relation strength of each variable with other nominal variable (C as the coefficient of contingency). From the chi square method, difference from the SME before and after the Export English course training is expected to be found. The training will use classroom method. The title of this study is prepare SME in Facing AEC 2015 through English training program to obtain the export market.